A Review of the Little Known Ethnic Religious Art and Culture of Arunachal Pradesh, North-East India - Bina Gandhi Deori (Center for Research and Development of Religious Literature and Heritage, 2015)
Arunachal Pradesh, the north-easternmost state of India is a mountainous terrain inhabited by a number of ethnic communities. Due to its geographical isolation, it is still cut off from mainstream India and has limited interaction with the rest of India. There are as many as 26 major tribes and several hundred sub-tribes. They have their own distinct culture, tradition and religious belief system. Some of the ethnic communities namely, Apatani, Nyishi, Galo, Tagin, Tangsa, Wancho, Mishmi etc. have their indigenous religious practices with well-defined belief system but due to limited research there is a paucity of data which fails to present a clear picture of the culture and tradition of the ethnic communities of the region. In many ways, their indigenous religion plays an important role in influencing the peoples’ arts and culture. This paper is an attempt to review the ethnic religious art and culture of the people of Arunachal Pradesh in an effort to highlight and preserve their ethnic cultural identity.